Cadmium mobility in a circular food-to-waste-to-food system and the use of a cultivated mushroom (Agaricus subrufescens) as a remediation agent - Stoknes, K; Scholwin, F; Jasinska, A; Wojciechowska, E; Mleczek, M; Hanc, A; Niedzielski, P (Journal of environmental management, 2019)
Cadmium (Cd) and its mobility and toxicity in the food chain receives considerable public and scientific attention. Levels in soil have been increasing, partly caused by mineral fertiliser use. In many areas in the EU, intake of Cd is not far from the maximum tolerable level. Now, urban and more circular approaches to food production are being promoted, in which waste materials substitute growing media and fertilizers. Can this make the situation worse, or is it, on the contrary, possible to extract Cd from the cycle using practical microbial methods? Cd concentration, availability and accumulation in materials and crops in a closed greenhouse system was investigated first. Secondly, we tested if fungal remediation was able to remove a significant amount of Cd. A sequential extraction analysis showed how anaerobic digestion and composting changed chemical Cd availability. Cd levels in the system were comparable to agricultural soils. The vegetable crops did not accumulate Cd. However, the culture of the edible mushroom Agaricus subrufescens in the greenhouse had a strong effect on Cd mobility: It extracted 80% of the Cd from the growing medium into the mushrooms, mostly at the start of fruiting. These early Cd enriched mushrooms can be treated as special waste, while the later harvest complied with EU Cd limits for foodstuffs and can potentially be consumed. Thus, growing this mushroom species in an integrated waste-to-crop system can be a cost-efficient way to remediate Cd from the food chain.
Keywords: Fertilizers; Soil; půda; kadmium; průmyslová hnojiva; Agaricus; zemědělství; Agriculture; Cadmium